PENGARUH LITERASI KEUANGAN, FINANCIAL SELF EFFICACY, LOCUS OF CONTROL, DAN FINTECH PAYMENT TERHADAP PERILAKU MANAJEMEN KEUANGAN MAHASISWA DI SOLORAYA - Lusi Endah Mawarni; Ari Susanti (Lembaga Pengembangan Kinerja Dosen, 2025)
Financial digitalization shows significant developments in financial technology, and has an important impact on financial management of the community, especially students. This study aims to investigate the influence of financial literacy, financial self-efficacy, locus of control, and the use of fintech payments on students' financial management behavior. This study uses a quantitative approach involving a population of 100 active students surveyed in the Soloraya area. This study found that financial literacy, financial self-efficacy, locus of control, fintech payments have an effect on students' financial management behavior